1965
DOI: 10.2136/sssaj1965.03615995002900060022x
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient Cation Complexes in Soil Solution: Partition Between Complexed and Uncomplexed Forms by Solvent Extraction

Abstract: Procedures were developed for the partition of heavy metals (Cu, Co, and Zn) between complexed and uncomplexed forms in soil solution. Competition for the above cations by complexing agents naturally present in soil solution and added complexing agents that form metal complexes soluble in organic solvents was determined by measuring the distribution of metal between aqueous and organic phases in a two-phase system. The degree to which the metal was complexed in the original soil solution could be deduced by co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

1972
1972
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(29 citation statements)
references
References 0 publications
2
27
0
Order By: Relevance
“…Nevertheless, given our knowledge on the uptake of Co from simple solution culture studies, it would generally be expected that an increase in aqueous concentrations of Co would result in increased plant Co uptake (Bakkaus et al 2005;Chatterjee et al 2006;Gopal et al 2003;Homer et al 1991;Li et al 2009;Liu et al 2000;Tewari et al 2002;Wilson and Reisenauer 1963). This relationship in soils will be, however, confounded by Co complexation (Hodgson et al 1965;Merckx et al 1986;Sanders 1983) based on our knowledge that complexation, whether by plant-or microbially-derived organic ligands, may 1) reduce metal uptake by plants when grown in solution culture (McLaughlin et al 1997) or 2) increase Co uptake from soils as a result of increased flux to the root surface by mass flow or diffusion processes (Adriano et al 1977;Hodgson 1981;Wallace and Mueller 1973). This is also demonstrated in the study of Li et al (2009) where shoot Co concentrations varied by two orders of magnitude despite soil solution concentrations remaining constant.…”
Section: Soil Solution Co Concentrations and Speciationmentioning
confidence: 99%
“…Nevertheless, given our knowledge on the uptake of Co from simple solution culture studies, it would generally be expected that an increase in aqueous concentrations of Co would result in increased plant Co uptake (Bakkaus et al 2005;Chatterjee et al 2006;Gopal et al 2003;Homer et al 1991;Li et al 2009;Liu et al 2000;Tewari et al 2002;Wilson and Reisenauer 1963). This relationship in soils will be, however, confounded by Co complexation (Hodgson et al 1965;Merckx et al 1986;Sanders 1983) based on our knowledge that complexation, whether by plant-or microbially-derived organic ligands, may 1) reduce metal uptake by plants when grown in solution culture (McLaughlin et al 1997) or 2) increase Co uptake from soils as a result of increased flux to the root surface by mass flow or diffusion processes (Adriano et al 1977;Hodgson 1981;Wallace and Mueller 1973). This is also demonstrated in the study of Li et al (2009) where shoot Co concentrations varied by two orders of magnitude despite soil solution concentrations remaining constant.…”
Section: Soil Solution Co Concentrations and Speciationmentioning
confidence: 99%
“…Most other chelating agents investigated failed to demonstrate stability comparable to the natural Fe 3 + complex. Based on existing evidence, then, it appears that dissolved metals such as Fe 3 + and Cu2+ are almost completely in organically complexed form (Hodgson et al, 1965;McBride and Blasiak, 1979;B.R. James and Bouldin, 1986).…”
Section: Speciation Of Metals In Solutionmentioning
confidence: 99%
“…However, as can be deduced from Figure 19, the fraction of Cu2+ in the complexed relative to free form diminishes at lower pH, and this type of behavior is likely for most complexing metals. Metals such as Co 2 +, Cd2+, and Zn2+, because of their lesser tendencies to form soluble complexes with oxygen-containing functional groups of soluble organic matter, are complexed to a smaller degree in soil solution (Hodgson et al, 1965;McBride and Blasiak, 1979;Tyler and McBride, 1982). For example, between 13% and 43% of Zn in acid soil solutions has been reported in exist in labile form (B.R.…”
Section: Speciation Of Metals In Solutionmentioning
confidence: 99%
“…This chemical feature of HS improves physical soil properties favoring the formation of stable clay-humic aggregates through cation bridges, and soil fertility increasing mineral nutrient (P, Fe, Mn or Zn) availability for plants grown in alkaline and calcareous soils [15]. In fact, several studies have reported that a very significant fraction of Cu, Zn, Fe and Mn in soil solution from limy, alkaline soils was present in the form of complexes with DOM [16][17][18].…”
Section: Main Hs-ie On Plant Growth and Mineral Nutritionmentioning
confidence: 99%